Therapeutically targeting type I interferon directly to XCR1+ dendritic cells reveals the role of cDC1s in anti-drug antibodies - Noe, Paul; Wang, Joy H.; Chung, Kyu; Cheng, Zhiyong; Field, Jessica J.; Shen, Xiaomeng; Casey, Stephanie C.; Cortesio, Christa L.; Pastuskovas, Cinthia V.; Phee, Hyewon; Tarbell, Kristin V.; Egen, Jackson G.; et al. (Frontiers in Immunology, 2023)
Conventional type 1 dendritic cells (cDC1s) are superior in antigen cross-presentation and priming CD8 + T cell anti-tumor immunity and thus, are a target of high interest for cancer immunotherapy.Type I interferon (IFN) is a potent inducer of antigen cross-presentation, but, unfortunately, shows only modest results in the clinic given the short half-life and high toxicity of current type I IFN therapies, which limit IFN exposure in the tumor. CD8 + T cell immunity is dependent on IFN signaling in cDC1s and preclinical studies suggest targeting IFN directly to cDC1s may be sufficient to drive anti-tumor immunity. Here, we engineered an anti-XCR1 antibody (Ab) and IFN mutein (IFN mut ) fusion protein (XCR1Ab-IFN mut ) to determine whether systemic delivery could drive selective and sustained type I IFN signaling in cDC1s leading to anti-tumor activity and, in parallel, reduced systemic toxicity. We found that the XCR1Ab-IFN mut fusion specifically enhanced cDC1 activation in the tumor and spleen compared to an untargeted control IFN. However, multiple treatments with the XCR1Ab-IFN mut fusion resulted in robust anti-drug antibodies (ADA) and loss of drug exposure. Using other cDC1-targeting Ab-IFN mut fusions, we found that localizing IFN directly to cDC1s activates their ability to promote ADA responses, regardless of the cDC1 targeting antigen. The development of ADA Targeted cDC1 activation enhances ADA 2 This is a provisional file, not the final typeset article remains a major hurdle in immunotherapy drug development and the cellular and molecular mechanisms governing the development of ADA responses in humans is not well understood. Our results reveal a role of cDC1s in ADA generation and highlight the potential ADA challenges with targeting immunostimulatory agents to this cellular compartment.